Design and analysis of actual and alternative exhaust gas recirculation systems on Solar Turbines Centaur 40 3.5MWe gas turbine engine for the purpose of carbon capture optimization - Jeremiah, Bianca R., author; Windom, Bret, advisor; Bandhauer, Todd, committee member; Herber, Daniel, committee member (Colorado State University. Libraries, 2025)
Power generation plants on land as well as in marine applications are massively contributing to carbon dioxide emissions, causing accelerated climate change throughout the globe. Decarbonization of the energy production industry is imperative, especially as energy demand continues to grow. As the power grid decarbonizes through new energy solutions and alternative technologies, retrofitting the current power generation system is an essential step in bridging the existing infrastructure with the emerging one. One way to bridge the gap is by retrofitting existing engines with exhaust gas recirculation systems for improved carbon capture capability. This work discusses the design and deployment implications of an EGR system on a 3.5 MWe Solar Turbines Centaur 40 gas turbine at Colorado State University (CSU), utilizing Flownex simulation software to model various system configurations. System requirements and design considerations of a gas turbine EGR system are presented, along with detailed analysis of a bottled gas manifold that will serve as a surrogate of an EGR system. Detailed analysis of the cooling load, footprint, and steam production associated with multiple cooling systems are explored as it pertains to actual EGR systems, as well as the combustion composition of the recirculated exhaust gases. For the surrogate EGR system, careful consideration of the required gas mass flow rates to reproduce the expected EGR composition is taken with respect to available bulk delivery capacities and delivery technology. Both natural gas and diesel fuel compositions are considered in system models to develop the EGR system as an applicable technology on both land and marine based gas turbine power production plants. The optimal system design for applying EGR to CSU's Solar Turbines Centaur 40 gas turbine engine was determined to be the surrogate gas system, as it avoids high cooling loads and space requirements that would be restrictive if attempted in the available research facility. An exhaust gas system was constructed to enable future experimental testing of the surrogate EGR system, which includes both internal and external building modifications.
Keywords: EGR; gas turbine; exhaust gas recirculation; decarbonization